Educational intervention for informal caregiver of person with dementia: a systematic review - Zulkifley, Nuraisyah Hani; Ismail, Suriani; Abdul Manaf, Rosliza; Lim, Poh Ying (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
The role of caregivers is very important in the management of person with dementia, where it is not uncommon for them to experience psychological distress. However, the level of distress can be managed and reduced through strategic educational intervention. A systematic review has been conducted through searching Medline, Science direct, Cochrane library and EMBASE databases to provide a narrative synthesis that elaborate on methods and outcomes of the educational intervention among informal caregiver of person with dementia. From a total of 5125 records, eight studies were selected and included in this review, where the results show that educational intervention can be implemented either as individual or group intervention. Group intervention methods mainly focus on training programs such as workshops and lectures, and also group-based discussions. While for individual intervention, most of the activities were implemented through self-learning using technology or computer-based systems. In conclusion, based on the outcome of the studies, both methods of implementations are found to be useful in reducing psychological distress of the informal caregiver.